HRD-negative high-grade carcinoma of the ovary in BRCA2 pathogenic variant carrier - A. P. Sokolenko; S. V. Poletaeva; A. D. Shestakova; T. V. Gorodnova; I. V. Berlev; E. N. Imyanitov (Сибирский онкологический журнал)
Background. Homologous recombination deficiency (HRD) is a valuable molecular marker for predicting response to platinum agents and poly(ADP-ribose)-polymerase (PARP) inhibitors. Germline and somatic alterations in the BRCA1 and BRCA2 genes are the major cause of HRD in ovarian cancer. However, in some cases, tumors arising in carriers of BRCA1 or BRCA2 pathogenic variants do not lose the normal copy of the corresponding gene and are not deficient for homologous recombination. Aim of the study was to present a case of high-grade ovarian carcinoma without HRD phenotype developed in a BRCA2 mutation carrier. Case report. A 48-year-old woman was diagnosed with multiple primaries: HER2-positive high-grade ovarian cancer and colorectal adenocarcinoma. analysis of the coding BRCA1/BRCA2 sequences revealed the germline BRCA2 c.658_659delgt [rs80359604] pathogenic variant. Given the unusual histological features, namely the absence of serous or endometrioid markers and high HER2 expression, we performed additional molecular analysis of the metastatic lesions in the lymph nodes. In all samples, the pattern of chromosomal instability did not match the HRD profile and there was loss of the mutant copy of the BRCA2 gene. Therefore, this tumor lacked the BRCAness phenotype. Conclusion. Tumors arising in HRR gene mutation carriers require additional molecular analysis for a comprehensive assessment of HRD.